Determination of abandoned land as a form of government supervision of land rights holders based on government regulation number 20 of 2021 concerning the control of abandoned areas and land - Fadhya, Namira Fadhya; Parwitasari, Hendriani (Trigin Publisher, 2024)
Government regulation on abandoned land as specified in Government Regulation No. 20 of 2021 is still relatively weak. Government supervision of land rights holders has not been regulated in detail, especially regarding how the government ensures that the land is used as intended. In addition, at the inventory stage, there are no provisions regarding the reporting period of land rights holders, whether the reporting should be done monthly or annually. This lack of clarity has the potential to cause conflicts such as potential social conflicts that will occur in the taking of land rights. This paper aims to examine the criteria and qualifications for determining abandoned land by the government as well as the forms of supervision that have not been regulated in Government Regulation No. 20 of 2021. It is hoped that this paper can provide proposed norms to create legal certainty and be useful in resolving land disputes in Indonesia. The result of this writing is that supervision by the government is still needed on the exclusion of abandoned land objects to ensure that the land is actually utilized properly in accordance with Article 4 of the UUPA. In addition, there are still weaknesses in PP No.20 of 2021, in that there are no rules, time frames, and obligations to report on the condition of land utilization for holders of property rights to land that are different from the obligations of other rights holders. This situation reflects inequality in regulation between different types of land rights, which can lead to land conflicts due to differences in supervision by the government of land rights holders.